Biodegradable Polymers Based on Cellulose and Fiber from Coffee (Coffea spp.) and Sugarcane (Saccharum spp.) Residues - Itzel Galaviz-Villa; Irving David Pérez Landa; Guadalupe D. Gutiérrez Sampieri; Virginia Alcántara-Méndez; Magnolia Gricel Salcedo-Garduño; Marybel A. Castillo-Ferat (BioResources)
Agro-industrial residues, derived from cereals, fruits, and vegetables, comprise non-consumable byproducts, including stems, leaves, peels, and seeds. Globally, approximately 3,045 million tons of such material is generated annually. In Mexico, the industrial crops coffee (Coffea spp.) and sugarcane (Saccharum spp.) yield residues rich in structural components, including lignin, cellulose, and hemicellulose. This study determined the physicochemical characteristics of cellulose isolated from these residues to formulate biodegradable polymers. Cellulose isolation was performed through chemical bleaching treatments, alkaline hydrolysis, and acid hydrolysis, yielding high-purity α-cellulose at 88.8% for coffee husks and 83.3% for sugarcane bagasse, with yields of 32.8% and 29.4%, respectively. Two biopolymers were developed: (A) 100% coffee husk cellulose and (B) a composite of 75% sugarcane bagasse fiber and 25% coffee husk cellulose. Biopolymer A demonstrated superior physicochemical properties, including moisture content, water vapor permeability, and solubility. Biodegradability assessments confirmed that both biopolymers were compostable within 110 days, exhibiting degradation extents of 84.4% (A) and 77.5% (B), primarily converting into organic matter and CO₂. These findings indicate that coffee and sugarcane agro-industrial residues are viable feedstocks for sustainable biopolymer production.